Association Between Antibiotic Treatment and the Efficacy of Intravesical BCG Therapy in Patients With High-Risk Non-Muscle Invasive Bladder Cancer - Pak, Sahyun; Kim, Sun-Young; Kim, Sung Han; Joung, Jae Young; Park, Weon Seo; Chung, Jinsoo; Lee, Kang Hyun; Seo, Ho Kyung (Frontiers in Oncology, 2021)
Objective: To investigate the association between antibiotic therapy and the efficacy of intravesical BCG therapy in patients with high-risk non-muscle invasive bladder cancer (NMIBC). Methods: This study involved the retrospective review of medical records of patients who underwent transurethral resection of bladder tumors for high-risk NMIBC followed by intravesical BCG therapy between 2008 and 2017. Patients were categorized as none, short- (2-6 days), and long-course use (≥7 days) based on the duration of antibiotic treatment concurrent with or initiated ≤30 days before BCG therapy. Oncologic outcomes, including recurrence-free survival and progression-free survival, were analyzed. Results: Of the 276 patients enrolled in the study, 162 (58.7%) had pathologic T1 disease and 206 (80.2%) had high-grade disease. Concurrently with or prior to BCG therapy, 114 patients had (41.3%) received short-course antibiotic therapy, and 96 (34.8%) patients had received long-course antibiotics. The 5-year recurrence-free survival (62.2% vs 26.9%; log rank, p <0.001) and progression-free survival (79.6% vs. 53.3%; log rank, p=0.001) rates were significantly higher in patients who did not receive antibiotic therapy than in those treated with long-course antibiotics. Multivariable analysis revealed that antibiotic treatment for more than 7 days was independently associated with increased risks of recurrence (hazard ratio [HR], 2.45; 95% confidence interval [CI], 1.49-4.05; p < 0.001) and progression (HR, 3.68; 95% CI, 1.65-8.22 p = 0.001). Conclusion: Long-course antibiotic treatment concurrently with or prior to intravesical BCG adversely influenced disease recurrence and progression outcomes in patients with high-risk NMIBC. Careful use of antibiotics may be required to enhance the efficacy of intravesical BCG therapy. Further mechanistic and prospective studies are warranted.